Peran Zinc sebagai Imunomodulator pada Pasien COVID-19 - Pamela B. Ratela; Youla A. Assa; Murniati Tiho (Universitas Sam Ratulangi, 2022)
Abstract: Consumption of micronutrients is essential for maintaining optimal health. Zinc can act as an immunomodulator and is a compound that can interact with the immune system. Coronavirus Disease 2019 (COVID-19) is a disease caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). Until now, there is no specific treatment for COVID-19, because theÂ has self-limiting properties, so the healing process is influenced by immunity. Various efforts have been made as prevention, one of them being related to nutrition. During the COVID-19 pandemic, immunostimulants are needed to increase the bodyâ€™s immunity against viral infections. The purpose of this study was to determine the role of zinc as an immunomodulator in COVID-19 patients. This research is in the form of a literature review using three databases, namely Pubmed, Science Direct, and Clinical Key. The keywords used in the article search were zinc OR seng AND immunomodulator AND COVID-19. After being selected based on inclusion and exclusion criteria, there were 10 literatures that met the criteria. The results obtained from all studies show that zinc has a role as an immunomodulator in COVID-19 patients. In conclusion, zinc therapy has benefits as an immunomodulator in COVID-19 patients.Keywords: zinc; COVID-19Â Abstrak: Konsumsi mikronutrien sangat penting untuk menjaga kesehatan yang optimal. Zinc dapat berperan sebagai imunomodulator dan merupakan senyawa yang dapat berinteraksi dengan sistem imun. Coronavirus Disease 2019 (COVID-19) merupakan penyakit yang disebabkan oleh Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). Hingga saat ini tidak ada tatalaksana khusus dalam pengobatan COVID-19, karena virus memiliki sifat self-limitting, sehingga proses penyembuhan dipengaruhi oleh imunitas. Berbagai upaya dilakukan sebagai pencegahan, salah satunya terkait dengan gizi. Di masa pandemi COVID-19 ini, dibutuhkan imunostimulan agar dapat meningkatkan kekebalan tubuh dalam infeksi virus. Tujuan penelitian ini untuk mengetahui peran zinc sebagai imunomodulator pada pasien COVID-19. Penelitian ini berbentuk literature review menggunakan tiga database yaitu Pubmed, Science Direct dan Clinical Key. Kata kunci yang digunakan dalam pencarian artikel yaitu zinc OR seng AND COVID-19. Setelah diseleksi berdasarkan kriteria inklusi dan eksklusi, didapatkan 10 literatur yang memenuhi kriteria. Hasil yang didapatkan dari semua studi menunjukkan bahwa zinc memiliki peran sebagai imunomodulator pada pasien COVID-19. Kesimpulan, terapi zinc memiliki manfaat sebagai imunomodulator pada pasien COVID-19.Kata kunci: zinc; COVID-19